Cost of treating hypertension in Malaysia - Al-Efan, Qais Muhammad Ahmad (2009)
Background: Cost of illness studies approximate the economic burden of any disease on the society. Hypertension is one of the most prevalent vascular diseases and is considered as a main risk factor for cardiovascular diseases. Hypertension is greatly prevalent and severe in Malaysia. Its care is insufficient. Hypertension detection and treatment is less than satisfactory in Malaysia.